The Manhaj of Muhammadiyah Progressive Islam: Theological, Philosophical, and Ethical Perspectives - M. Amin Abdullah (Universitas Muhammadiyah Malang, 2024)
This article examines the Progressive Islamic Manhaj initiated by Muhammadiyah as Indonesia's largest modern Islamic organization. The method or manhaj was formulated by Muhammadiyah as a serious effort to transform Islamic movements and thoughts that are modern and responsive to the development of the times. In its review, this study complements its discussion with theological, philosophical, and ethical perspectives in viewing and providing answers to various contemporary social, political, and religious problems that are increasingly complicated. Moreover, the urgency of the Muhammadiyah Progressive Islamic Manhaj is needed to respond to the invitation to religion in a strict, rigid, narrow, and closed manner carried out by certain groups in the name of religion, both orally, in writing, and creative approaches on social media. This research article uses a descriptive analysis method for various socio-theological problems faced by the Muslim community in Indonesia. Then, this article would like to explain a vital approach initiated by Muhammadiyah, namely the Progressive Islamic Manhaj, by updating the interpretation of the five main principles of maqāṣid sharī‘ah as a solution to contribute to the solution of various socio-religious problems. In the end, this study concludes that it is essential for Muhammadiyah to reform the basic epistemology of Islamic legal thought, especially those related to social life at large, especially with the spread of procedural reasoning religious perspectives or al-‘aql al-ijrā’ī in Fiqh and Kalām and legal-formal religious fatwa reasoning or al-‘aql al-iftā’ī, which seems to close the meetings of the universal values of humanity listed in the Qur'an.